Synchronous occurrence of primary right ovarian endometrioid adenocarcinoma and primary left ovarian clear cell adenocarcinoma: A case report. Issue 27 (July 2018) - Zhao, Ling-jun; Wang, Ping; He, Ying
Abstract: Rationale: Ovarian malignancy is associated with one of the highest rates of death among gynecological reproductive system malignancies. While progress has been made in surgical and postoperative adjuvant treatment approaches, the early atypical clinical manifestations, quick progression, and lack of the effective early screening means imply that the prognosis remains poor. Bilateral ovarian cancers are common, but different types of primary bilateral ovarian carcinomas are extremely rare. Patient concerns: According to clinical pathologic, immunohistochemistry, and medical imaging data, a 51-year-old Chinese woman with abdominal pain was diagnosed as having right ovarian well-differentiated endometrioid adenocarcinoma with mucinous adenocarcinoma and left ovarian clear cell adenocarcinoma. Diagnoses: Immunohistochemistry confirmed the diagnosis of primary bilateral ovarian cancers. Interventions: She received multimodal treatment including surgery and chemotherapy. Outcomes: The patient's recovery was uneventful, and she responded well to the chemotherapy. Lessons: We speculate that the different types of primary bilateral ovarian carcinomas presented in this case may be due to different malignant transformations of the endometriotic lesions. Therefore, clinicians should pay special attention to the possible malignant transformation of endometriosis.